1992
DOI: 10.1182/blood.v79.9.2237.2237
|View full text |Cite
|
Sign up to set email alerts
|

Experience with protein A-immunoadsorption in treatment-resistant adult immune thrombocytopenic purpura

Abstract: Extracorporeal immunoadsorption of plasma to remove IgG and circulating immune complexes (CIC) was evaluated as a therapy for adults with treatment-resistant immune thrombocytopenic purpura (ITP). Seventy-two patients with initial platelet counts less than 50,000/microL who had failed at least two other therapies were studied. They received an average of six treatments of 0.25 to 2.0 L plasma per procedure over a 2- to 3-week period using columns of staphylococcal protein A-silica (PROSORBA immunoadsorption tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…After approval for ITP was granted by the Food and Drug Administration in 1987, Imre launched a Save the Spleen (I still have the packet!) campaign showing 40 to 50% response rates for adult chronic ITP, adult acute ITP, pediatric/adolescent ITP, and HIV associated thrombocytopenia (14). Interestingly, some of the patients in these studies also had systemic lupus.…”
Section: Membranes Immune Adsorption and Ramentioning
confidence: 80%
“…After approval for ITP was granted by the Food and Drug Administration in 1987, Imre launched a Save the Spleen (I still have the packet!) campaign showing 40 to 50% response rates for adult chronic ITP, adult acute ITP, pediatric/adolescent ITP, and HIV associated thrombocytopenia (14). Interestingly, some of the patients in these studies also had systemic lupus.…”
Section: Membranes Immune Adsorption and Ramentioning
confidence: 80%
“…Immunoadsorption has been used in the treatment of many autoimmune diseases, which remain unresponsive to other therapies. Idiopathic thrombocytopenic purpura, hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, and myasthenia gravis are examples of autoimmune disorders with good response on treatment with extracorporeal therapy [5][6][7][8]. The bridging of infectious complications described here has similarities with using immunoadsorption for infectious complications in severe pemphigus, which has been also successfully done with tryptophan immunoadsortion [9].…”
Section: Discussionmentioning
confidence: 99%
“…SPA column immunoadsorption therapy has been shown to have a 30‐ to 50‐percent response rate in the treatment of refractory ITP 3 . This therapy is generally indicated in patients with ITP who have failed at least two therapies, that is, steroids and an immunosuppressive chemotherapeutic regimen, and have platelet counts less than 50 × 10 9 per L. To prevent the activation of coagulation as plasma comes in contact with the silica matrix in the column, heparinized saline is used to prime the column.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoadsorption therapy using staphylococcal protein A (SPA) columns removes IgG (IgG 1 , IgG 2 , IgG 4 ) and IgG‐containing, circulating immune complexes from plasma 1,2 . Clinical studies indicate that this therapy is 30 to 50 percent effective in the treatment of refractory idiopathic thrombocytopenia purpura (ITP) 3 . Several studies have shown that this therapy may be effective in the treatment of refractory alloimmune thrombocytopenia and in the management of refractory rheumatoid arthritis 4–7 …”
mentioning
confidence: 99%